Evaluating the impact of cycle helmet use on severe traumatic brain injury and death in a national cohort of over 11000 pedal cyclists: a retrospective study from the NHS England Trauma Audit and Research Network dataset. Issue 9 (13th September 2019) - Dodds, Nick; Johnson, Rowena; Walton, Benjamin; Bouamra, Omar; Yates, David; Lecky, Fiona Elizabeth; Thompson, Julian
Abstract : Objectives: In the last 10 years there has been a significant increase in cycle traffic in the UK, with an associated increase in the overall number of cycling injuries. Despite this, and the significant media, political and public health debate into this issue, there remains an absence of studies from the UK assessing the impact of helmet use on rates of serious injury presenting to the National Health Service (NHS) in cyclists. Setting: The NHS England Trauma Audit and Research Network (TARN) Database was interrogated to identify all adult (≥16 years) patients presenting to hospital with cycling-related major injuries, during a period from 14 March 2012 to 30 September 2017 (the last date for which a validated dataset was available). Participants: 11 192 patients met inclusion criteria. Data on the use of cycling helmets were available in 6621 patients. Outcome measures: TARN injury descriptors were used to compare patterns of injury, care and mortality in helmeted versus non-helmeted cohorts. Results: Data on cycle helmet use were available for 6621 of the 11 192 cycle-related injuries entered onto the TARN Database in the 66 months of this study (93 excluded as not pedal cyclists). There was a significantly higher crude 30-day mortality in un-helmeted cyclists 5.6% (4.8%–6.6%) versus helmeted cyclists 1.8% (1.4%–2.2%) (p<0.001). Cycle helmet use was also associated with a reduction in severe traumatic brain injury (TBI) 19.1% (780, 18.0%–20.4%) versus 47.6% (1211, 45.6%–49.5%) (p<0.001), intensive care unit requirement 19.6% (797, 18.4%–20.8%) versus 27.1% (691, 25.4%–28.9%) (p<0.001) and neurosurgical intervention 2.5% (103, 2.1%–3.1%) versus 8.5% (217, 7.5%–9.7%) (p<0.001). There was a statistically significant increase in chest, spinal, upper and lower limb injury in the helmeted group in comparison to the un-helmeted group (all p<0.001), though in a subsequent analysis of these anatomical injury patterns, those cyclists wearing helmets were still found to have lower rates of TBI. In reviewing TARN injury codes for specific TBI and facial injuries, there was a highly significant decrease in rates of impact injury between cyclists wearing helmets and those not. Conclusions: This study suggests that there is a significant correlation between use of cycle helmets and reduction in adjusted mortality and morbidity associated with TBI and facial injury.